Network Text Analysis for Marketing Intelligence: Deconstructing the 'Gamis' Word Association Network using Modularity and Centrality Metrics - Adi Prasetyo (Program Studi Informatika Universitas PGRI Yogyakarta, 2025)
The proliferation of unstructured textual data on social media offers a rich repository for marketing intelligence, yet the extraction of actionable insights remains challenged by the high volume of noise and the limitations of frequency-based text mining. This study proposes a Network Text Analysis (NTA) framework to examine the semantic topology of online conversations regarding